Design Of a Web-Based School Operational Assistance (Bos) Management Information System at SMA Negeri 1 Nggaha Ori Angu - Melda Kareri Hara; Yustina Rada; Erwianta Gustial Radjah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The management of School Operational Assistance (BOS) funds is an annual obligation for educational institutions. The Treasurer is responsible for this activity, which is overseen by the Principal. However, at SMA Negeri 1 Nggaha Ori Angu, the School Operational Assistance (BOS) fund management system is still conducted using a physical ledger. This process has encountered several challenges, including the difficulty in calculating the total funds managed and the lack of efficiency in managing the School Operational Assistance (BOS) funds. The process of utilising the ledger currently results in the unnecessary expenditure of time and effort, in addition to a considerable risk of errors and inaccuracies in the recorded data. In light of the challenges encountered in the management of School Operational Assistance (BOS) funds at SMA Negeri 1 Nggaha Ori Angu, this research aims to develop an Information System for the Management of School Operational Assistance Funds (BOS) using the Rapid Application Development (RAD) method. The web development in this research will employ the Hypertext Preprocessor (PHP) programming language with the CodeIgniter framework, which implements the Model-View-Control (MVC) concept. This technology has the potential to optimize and enhance the quality of School Operational Assistance (BOS) fund management at SMA Negeri 1 Nggaha Ori Angu.